Response Surface Approach for Optimization of Protein Hydrolysis from Reutealis trisperma Cake as Potential Animal Feedstock - Yuana Elly Agustin; Lieke - Riadi; Titie Prapti Utami (Reaktor, 2020)
The conditions for protein hydrolysis were optimized to prepare Reutealis trisperma cake for potential animal feedstock. The cake’s content was 34.03 % protein, 6.32 % moisture, 18.56 % total sugar, 15.58 % lipid and 25.51% others. Other components in cake could be fibre and lignin. The cake is a byproduct of mechanical pressing process of the seeds and contains high protein content (34.03%). It was ground prior the hydrolysis process. A central composite design including concentration of NaOH, ratio of cake to NaOH, time and temperature were used to develop second order model to predict protein content under various experimental conditions. Protein yield was primarily affected by ratio pressed cake to NaOH and concentration of NaOH. Based on the Response Surface Methodology (RSM) model, maximum yield of protein was 11.33% which was obtained at cake/solvent ratio 1: 50; 1.5 % w/v NaOH; 15 minutes of hydrolysis at 40oC. The actual maximum protein yield from the experiment was obtained at cake/solvent ratio 1: 40; 1.5 % w/v NaOH; 20 minutes of hydrolysis at 45oC which was 21.28 %.Keywords: animal feedstock; protein hydrolysis; response surface; Reutealis trisperma